2018
DOI: 10.2147/vhrm.s170317
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1, nitric oxide, serotonin and high blood pressure in male adolescents

Abstract: BackgroundEssential arterial hypertension (EAH) in adolescents represents a social burden. The endothelium is involved in the pathogenesis of EAH. Imbalance of key vasoactive factors – namely nitric oxide (NO) and endothelin-1 (ET-1) – is observed, and serotonin (5-HT) release is also impaired. The relationship between the factors and high blood pressure (BP) has been established mainly in preclinical studies and in the adult age. The aim of the present manuscript is to establish the association between plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
(44 reference statements)
2
20
0
2
Order By: Relevance
“…Оксид азота служит локальным тканевым регулятором, поддерживающим вазодилатацию [15,28]. В ранее проведенных исследованиях показано уменьшение его концентрации у подростков при стабильной артериальной гипертензии [20,29,30], ожирении [31,32], сахарном диабете [31], заболеваниях почек [32], что указывает на истощение вазодилатирующей функции эндотелия.…”
Section: Discussionunclassified
“…Оксид азота служит локальным тканевым регулятором, поддерживающим вазодилатацию [15,28]. В ранее проведенных исследованиях показано уменьшение его концентрации у подростков при стабильной артериальной гипертензии [20,29,30], ожирении [31,32], сахарном диабете [31], заболеваниях почек [32], что указывает на истощение вазодилатирующей функции эндотелия.…”
Section: Discussionunclassified
“…Все частіше визнається, що це пов'язано з АГ [2]. На найбільш ранніх етапах розвитку АГ в патологічний процес включається ендотелій судин, що виділяє ЕТ-1, який володіючи вазоконстрикторною дією, бере участь в регуляції судинного тонусу, підвищення якого відіграє важливу роль в розвитку і прогресуванні ряду серцево-судинних захворювань [3,4].…”
Section: вступunclassified
“…Several studies have reported on the role of these neurotransmitters in the pathophysiology of cardiovascular diseases (e.g., hypertension) [4454].…”
Section: The Role Of Monoamine Oxidase (Mao) In the Pathophysiologmentioning
confidence: 99%
“…High serotonin levels have been reported to play a role in the pathogenesis of cardiovascular diseases and hypertension [4454]. A study conducted by Aflyatumova et al looking at endothelin-1, nitric oxide, and serotonin in male adolescents showed that both endothelin-1 and serotonin serum concentration levels were increased in prehypertensive and hypertensive individuals compared to controls.…”
Section: The Role Of Monoamine Oxidase (Mao) In the Pathophysiologmentioning
confidence: 99%
See 1 more Smart Citation